THE RUSSIAN LANGUAGE IN ETHNOREGIONAL MULTILINGUAL ENVIRONMENT - Svetlana K. Bashieva; Marina Ch. Kremshokalova; Irina V. Shontukova (Moscow Polytechnic University, 2017)
The article addresses the issues concerning the peculiarities ofthe Russian language functioning in modern Russian ethnoregional and multilingual environment, including communicative and educational space. Special consideration is given to the questions of linguistic interference and intersection of semantic worlds of Russian and Caucasus enthocultures. The socially and culturally genetic functions of the Russian language forming the All-Russian identity are proved to come to the fore in ethnoregional and multicultural conditions. The authors substantiate the necessity of facilitating the Russian language learning in ethnoregional universities of Russia as well as of including Business Russian into the list of curriculum disciplines.